Building ASIPS: The Mescal Methodology - Gries, Matthias; Keutzer, Kurt.; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
An increasing number of system designers are using ASIP$1 (Bs rather than ASIC$1 (Bs to implement their system solutions. Building ASIPs: The Mescal Methodology gives a simple but comprehensive methodology for the design of these application-specific instruction processors (ASIPs). The key elements of this methodology are: Judiciously using benchmarking Inclusively identifying the architectural space Efficiently describing and evaluating the ASIPs Comprehensively exploring the design space Successfully deploying the ASIP This book includes demonstrations of applications of the methodologies using the Tipi research framework as well as state-of-the-art commercial toolsets from CoWare and Tensilica.s
and Motivation -- and Motivation -- The MESCAL Methodology for Building ASIPs -- Judiciously Using Benchmarking -- Inclusively Identifying the Architectural Space -- Efficiently Describing and Evaluating the ASIPs -- Comprehensively Exploring the Design Space -- Successfully Deploying the ASIP -- Using Commercial Tools to Apply the MESCAL Methodology for Building ASIPs -- Designing and Modeling MPSoC Processors and Communication Architectures -- Commercial Configurable Processors and the MESCAL Approach.
Keywords: Engineering; Engineering; Engineering, general; Electronic books